THE IMPACT OF INDONESIAN TERASI IN THE BEEF CONSOMMÉ, A SENSORY ASSESSMENT - Ambarita, Mery Tambaria Damanik (Metamorfosa: Journal of Biological Sciences, 2017)
The aim of this research was to investigate the impact of terasi , a traditional Indonesian condiment which is made from salted fermented seafood, on the sensory acceptance of beef consommé. Fifty four panelists compared the acceptance of beef consommé containing rebon terasi to the consommé containing fish terasi . The results showed that upon adjusting the salt content, the consommé containing rebon terasi was more preferred than the consommé containing fish terasi. By combining more strong spices or ingredients the acceptance of consommé might be improved while masking the pungent odor of terasi . In addition, six different types of rebon terasi varying in proximate composition, salt and water activity (a w ) were added to beef consommé and were evaluated by 10 trained panelists for their specific intensity of taste/flavor (saltiness, sourness, sweetness, bitterness, umami, fishy and rebon ) . Together with those samples, other consommés were also compared; however, the salt was also added to adjust with the highest salt content among six types of terasi. The results showed that variations of terasi influenced the sensory characteristics of consommé. The salt content of rebon terasi influenced the sourness, bitterness and saltiness in consommé, whilst the salt content should also reach the certain level to fit their acceptance. The distinct flavor from each terasi did have a profound effect on the sensory acceptability. The knowledge of the flavor characteristics of consommé and the role of terasi when mixed in consommé will help to improve the sensory acceptability and marketability of terasi .
Keywords: terasi, consommé, sensory analysis, flavor, taste